The representation of children in Garin Nugroho’s films - Wibawa, I Gusti Agung Ketut Satrya (Curtin University, 2008)
The image of the child has always been used for ideological purposes in national cinemas around the world. For instance, in Iranian cinema representations of children are often utilized to minimise the political risk involved in making radical statements, while in Brazilian and Italian cinemas children’s portrayal has disputed the idealized concept of childhood’s innocence. In Indonesian cinema, internationally acclaimed director Garin Nugroho is the only filmmaker who has presented children as the main focus of narratives that are oppositional to mainstream and state-sponsored ideologies. Yet, even though his films have been critically identified as key, breakthrough works in Indonesian cinema, no research so far has specifically focused on the representation of children in his films.Consequently, because Garin Nugroho has consistently placed child characters in central roles in his films, the discussion in this thesis focuses on the ideological and discursive implications of his cinematic depiction of children. With the central question regarding the construction of children’s identities in Garin’s films, the thesis analyzes in detail four of these films, dedicating an entire chapter to each one of them, and with the last one being specifically addressed in cinematic essay form. The films discussed are Surat untuk Bidadari (Letter to an Angel, 1993), Aku Ingin Menciummu Sekali Saja (2000), Rindu Kami Padamu (Of Love and Eggs,2004) and Daun di Atas Bantal (Leaf on a Pillow,1997).The textual analysis of films that is carried out is framed by two key ideas: firstly, Garin’s position as an auteur and, secondly, the specific ways in which he deploys representations of children against mainstream discursive constructions in Indonesia. Following the argument that Garin has used a form of ‘strategic intervention’ to explore particular political issues in Indonesia (Hanan 2004), the thesis identifies ways in which Garin deconstructs children’s images and provides alternatives to dominant discourses on childhood in Indonesia. Through the analysis of selected films, the thesis reveals that while the identities of children are constructed in his films against the idealized image of Indonesian children, they are also utilized by him to convey more broadly his political views about Indonesia.